Ultrathin-strut biodegradable polymer versus durable polymer drug-eluting stents: a meta-analysis. Issue 2 (12th October 2020) - Monjur, Mohammad Riashad; Said, Christian F; Bamford, Paul; Parkinson, Michael; Szirt, Richard; Ford, Thomas
Abstract : Objectives: Determine whether an ultrathin biodegradable polymer sirolimus-eluting stent ('Orsiro'—BP-SES) has clinical benefits over second-generation durable polymer drug-eluting stents (DP-DES). Methods: We conducted a prospective systematic review and meta-analysis of randomised clinical trials comparing Orsiro BP-SES against DP-DES (PROSPERO Registration: CRD42019147136). The primary outcome was target lesion failure (TLF): composite of cardiac death, target vessel myocardial infarction (TVMI) and clinically indicated target lesion revascularisation (TLR)) evaluated at the longest available follow-up. Results: Nine trials randomised 11 302 patients to either Orsiro BP-SES or DP-DES. At mean weighted follow-up of 2.8 years, the primary outcome (TLF) occurred in 501 of 6089 (8.2%) participants with BP-SES compared with 495 of 5213 (9.5%) participants with DP-DES. This equates to an absolute risk reduction of 1.3% in TLF in favour of Orsiro BP-SES (OR 0.82; 95% CI 0.69 to 0.98; p=0.03). This was driven by a reduction in TVMI (OR 0.80; 95% CI 0.65 to 0.98; p=0.03). There were no significant differences in other clinical endpoints: cardiac death, TLR and stent thrombosis. Conclusion: The Orsiro BP-SES shows promising clinical outcomes in patients undergoing percutaneous coronary intervention compared with contemporary second-generation DES at a short to medium term follow-up. More research is warranted to evaluate performance over a longer follow-up period and in different clinical and lesion subsets.